Role of GSK3 Signaling in Neuronal Morphogenesis - Kim, Yun Tai; Hur, Eun-Mi; Snider, William D.; Zhou, Feng-Quan (Frontiers in Molecular Neuroscience, 2011)
Glycogen synthase kinase 3 (GSK3) is emerging as a key regulator of several aspects of neuronal morphogenesis including neuronal polarization, axon growth and axon branching. Multiple signaling pathways have been identified that control neuronal polarization, including PI3K, Rho-GTPases, Par3/6, TSC-mTOR, and PKA-LKB1. However, how these pathways are coordinated is not clear. As GSK3 signaling exhibits crosstalk with each of these pathways it has the potential to integrate these polarity signals in the control neuronal polarization. After neurons establish polarity, GSK3 acts as an important signaling mediator in the regulation of axon extension and axon branching by transducing upstream signaling to reorganizion of the axonal cytoskeleton, especially microtubules. Here we review the roles of GSK3 signaling in neuronal morphogenesis and discuss the underlying molecular mechanisms.